Just-in-time, just-enough-time and horizon signalling protocols on optical burst switches - Kirci, Pinar; Zaim, A. Halim (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Optical burst switch (OBS) is considered to be a promising switch technology for the future network. In this paper, just-in-time (JIT), just-enough-time (JET) and horizon signalling schemes for OBS are presented. These signalling schemes run over a core dynamic wavelength division multiplexing (DWDM) network. The network is proposed to support IP, ATM and burst traffic. We apply the Poisson and self-similar models to identify inter-arrival times in these protocols and the burst contention is handled by burst dropping. As a result, the variety of the simulation results show the pros and cons of the evaluated JIT, JET and horizon signalling schemas.
Optica Applicata, Vol. 36, 2006, nr 1, s. 111-123
Keywords: optyka; dynamic wavelength division multiplexing (DWDM); just-in-time (JIT); just-enough-time (JET); horizon signalling protocols; optical burst switch (OBS)